A Pseudomonas syringae diversity survey reveals a differentiated phylotype of the pathovar syringae associated with the mango host and mangotoxin production. - Gutiérrez Barranquero, José Antonio; Carrión Bravo, Víctor José; Murillo, Jesús; Arrebola-Díez, Eva María; Arnold, Dawn L.; Cazorla-López, Francisco Manuel; De-Vicente-Moreno, Antonio (The American Phytopathological Society, 2013)
Pseudomonas syringae pv. syringae, the causal agent of bacterial apical necrosis (BAN) in mango crops, has been isolated in different mango-producing areas worldwide. An extensive collection of 87 P. syringae pv. syringae strains isolated from mango trees affected by BAN from different countries, but mainly from Southern Spain, were initially examined by repetitive sequence-based polymerase chain reaction (rep-PCR) to analyze the genetic diversity with an epidemiological aim. rep-PCR was powerful in assessing intrapathovar distribution and also allowing clustering of the P. syringae pv. syringae strains isolated from mango, depending on the isolation area. A clear pattern of clustering was observed for all the P. syringae pv. syringae strains isolated from mango distinct from strains from other hosts, including strains for the same geographical regions as the mango isolates. For this reason, a representative group of 51 P. syringae pv. syringae strains isolated from mango and other hosts, as well as some P. syringae strains from other pathovars, were further characterized to determine their possible genetic, phenotypic, and phylogenetic relationships. Similar to the rep-PCR results, the randomly amplified polymorphic DNA PCR (RAPD-PCR) and catabolic diversity analysis using the Biolog GN2 profile grouped 90% of the mango isolates together in a unique cluster. Interestingly, the majority of P. syringae pv. syringae strains isolated from mango produced mangotoxin. The analysis of the phylogenetic distribution using the multilocus sequence typing analysis strongly supports the existence of a differentiated phylotype of the pathovar syringae mainly associated with the mango host and characterized by the mangotoxin production.
Keywords: Pseudomonas; Bacillus (Bacteria); Mangos; Plantas - Enfermedades bacterianas; Bacteria; Pseudomonas syringae; Diversity; Mango; Mangotoxin